Policy transfer in elite sport development: the case of elite swimming in China - Tan, T.-C.; Zheng, J.; Dickson, G. (European Sport Management Quarterly, 2019)
Research question: This article explores policy transfer in the context of (non-professional) elite sport development through a detailed examination of Chinese elite swimming organisations since the early 2000s. The analysis is structured according to the five main aspects of policy transfer: rationale, actors, sources, elements and content, and conditioning factors. Research methods: Data were collected from 15 semi-structured interviews with officials, coaches and scholars. These interviews were complemented by a content analysis of official and semi-official documents from both relevant sports governing bodies and influential Chinese media. Results and findings: The major findings are that (1) the most important factors propelling the policy transfer were poor performances at major international sports events and a desire to be successful at the home Olympic Games; (2) the key policy transfer actors included government `insiders` and foreign experts; (3) Australia was the main source of new policy because of a combination of political, geographical, economic and sport-specific factors; (4) the policy content transferred focused mainly on ideas, methods and techniques rather than deeper-level structures and ideology; and (5) source nations sought to constrain the policy transfer process. Implications: Although policy transfer can be effective, there can be unintended negative consequences. Policy transfer is a bilateral process which is reliant upon the support of organisations or individuals from source nations. This research can stimulate elite sport programmes to consider the merits of pursuing policy transfer, when to pursue policy transfer and how to pursue policy transfer.